Integrating emotive competencies in public affairs education. (2nd October 2021) - Awasthi, Pallavi; Mastracci, Sharon H.
ABSTRACT: Emotion is the "how" of NASPAA competencies related to leading and managing in a culturally-conscious manner. In this article, we describe the role of emotion in public service and we detail the mechanism by which emotion fosters a collective mind-set for effective public service leadership and cultural literacy. We indicate specifically where emotive competencies could be integrated into the foundational skills demanded of all graduates of accredited programs. We further argue that they should be integrated into MPA core curricula. This normative argument captures the ethics of emotional labor: To graduate students from MPA programs without emotive capacities is to leave them poorly equipped for the practice of public service and to do so would be unethical. To demonstrate what is possible in public affairs education, we turn to an example from the Government of India Civil Service Competency Dictionary for a framework of emotive competencies in human resource management.